Examining the AHRD Standards on Ethics and Integrity Using a Multiple Ethical Paradigms Approach. (September 2014) - Kim, Taesung; Park, Jae-Young; Kolb, Judith A.
This research used a multiple ethical paradigms approach to examine the Standards on Ethics and Integrity ( Standards ) published by the Academy of Human Resource Development. After a thorough analysis of the current text of the Standards in terms of the four ethical paradigms of justice, care, community, and critique, we discuss issues and offer propositions to address those issues. Included within our discussion are the need for discussion forums on ethical issues, further reflection on a client- and community-centered approach in the Standards, and the introduction of professional language protocols and codes of Internet communications and technologies. We conclude this research with practical recommendations for updates, diffusion, and utilization of the Standards to enhance its further ethical contribution to the field of human resource development.